Penggunaan AI sebagai Media Pembelajaran pada Pendidikan Anak Usia Dini - Mutmainnah, Mutmainnah; Caroline, Novia; Margawati, Margawati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The goal of early childhood education is to prepare children to take the next level of education. This study examines the role of Artificial Intelligence (AI) as a learning medium in early childhood education (PAUD), which has significance in building the foundation of children's overall development. This study focuses on the use of AI in creating an adaptive, interactive, and responsive learning environment to the individual needs of children, including physical, cognitive, socio-emotional, language, and moral aspects. This study uses a narrative analysis method with a qualitative approach to various scientific articles and involves the views of educators, parents, and children in the PAUD environment. The results of the study indicate that AI is effective in providing personalized learning by adjusting the level of difficulty and content according to the child's needs. In addition, AI also supports the development of social skills through technology-based interactions and increases children's learning motivation through interesting and interactive experiences. The findings of this study indicate that AI-based media in PAUD learning can play a role in stimulating children's thoughts, feelings, attention, and competence. AI allows for more dynamic delivery of material and supports educators in managing more effective teaching strategies. Thus, the use of animation and AI-based technology as a learning tool provides significant benefits in increasing the effectiveness of teaching in PAUD